Successful treatment of iodixanol-induced type II Kounis syndrome with an intra-aortic balloon pump: a case report and literature review - Zhang, Naiju; Gao, Junran; Wang, Zhenjie; Chen, Tianping (Frontiers in Cardiovascular Medicine, 2025)
BackgroundKounis syndrome (KS) is an acute coronary syndrome triggered by hypersensitivity reactions and is often underrecognized in clinical practice. This report describes a case of iodixanol-induced KS that was refractory to standard emergency medications but successfully managed with an intra-aortic balloon pump (IABP), along with a review of similar published cases.Case summaryA 77-year-old woman with a history of chest pain underwent coronary angiography with iodixanol. During the procedure, she developed progressive bradycardia, hypotension, and convulsions. Despite immediate cardiopulmonary resuscitation and the administration of emergency medications, hypotension persisted. Hemodynamic stability was rapidly achieved following IABP implantation, with complete resolution of symptoms and no complications. This case represents the first reported instance of iodixanol-induced KS that was unresponsive to conventional vasoactive drugs and required IABP for stabilization. A review of the literature identified four prior cases of iodixanol-induced KS, all of which were successfully managed with medical therapy alone, highlighting the unique severity and therapeutic challenge of the present case.ConclusionThis is the first reported use of IABP for iodixanol-induced KS, suggesting its potential role in refractory cases.